Multiple Results to Some Biharmonic Problems - Xingdong Tang; Jihui Zhang (Abstract and Applied Analysis)
We study a nonlinear elliptic problem defined in a bounded domain involving biharmonic operator together with an asymptotically linear term. We establish at least three nontrivial solutions using the topological degree theory and the critical groups.